Brecht and curriculum: the Use of the Didactic Play Methodology in High School (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The article analyzed Bertolt Brecht's Didactic Play methodology and its application in High School education, aligning it with the Common National Curricular Base (BNCC). The study emerged in 2024 from discussions between the author and master's students, suggesting this approach as a teaching methodology. It involved practical experimentation, reflection, and curriculum analysis, concluding its suitability for developing BNCC competencies. The research advocates including the methodology in High School Arts teachers' course plans.
Keywords: didactic play; Bertolt Brecht; theater pedagogy; teacher training; high School